Upregulation of 11β-hydroxysteroid dehydrogenase 1 in lymphoid organs during inflammation in the rat - Ergang, Peter; Vytáčková, Kateřina; Svec, Jiří; Bryndová, Jana; Mikšík, Ivan; Pácha, Jiří (The Journal of steroid biochemistry and molecular biology, 2011)
Glucocorticoids exert anti-inflammatory and immunomodulatory effects that may be regulated in part by the activities of the glucocorticoid-activating and -inactivating enzymes, 11β-hydroxysteroid dehydrogenase type 1 (11HSD1) and type 2 (11HSD2), respectively. Previous studies have demonstrated that inflammatory bowel diseases in humans and experimental animals upregulate 11HSD1 and downregulate 11HSD2. We investigated whether proinflammatory cytokines modulate colonic 11HSDs as well as whether lymphoid organs exhibit any 11HSD response to inflammation. Colon tissue explants exposed to tumor necrosis factor α exhibited an upregulation of 11HSD1 mRNA whereas interleukin 1β downregulated 11HSD2 mRNA. Experimental colitis induced by the intracolonic administration of 2,4,6-trinitrobenzenesulfonic acid stimulated 11HSD1 activity not only in the colon but also in mesenteric lymph nodes and the spleen. Analysis of mRNA for 11HSD1 in colon-draining lymph nodes and the spleen showed that inflammation upregulates the expression of this enzyme in mobile lymphoid cells similar to the intraepithelial and lamina propria leukocytes isolated from the colon. It is inferred that inflammation stimulates the reactivation of glucocorticoids in lymphoid organs and in gut-associated lymphoid tissue.
Keywords: 11-beta-hydroxysteroiddehydrogenasa typ 1; lymfatické uzliny; RNA, Messenger; kolon; Male; Rats, Wistar; slezina; Up-Regulation; Tumor Necrosis Factor-alpha; Lymph Nodes; Colitis; mezenterium; upregulace; 11-beta-Hydroxysteroid Dehydrogenase Type 1; interleukin-1beta; mužské pohlaví; potkani Wistar; Spleen; krysa rodu Rattus; Trinitrobenzenesulfonic Acid; Animals; zvířata; Colon; Rats; Mesentery; Interleukin-1beta; kyselina trinitrobenzensulfonová; TNF-alfa; kolitida; messenger RNA